Highly conductive aligned carbon film for interconnect application - Li, Fushan (2021)
We demonstrate here an amorphous carbon film with a highly conductive transition phase for interconnect application. The uniform orientation of graphite-like sheet provides an effective carriers transport channel, thus significantly improves the conductivity of the amorphous carbon film. The electrical properties of the aligned carbon film are investigated using Kelvin structure. Our results show that the resistivity of aligned carbon film is comparable with that of Cu, and the aligned carbon film holds promise for future interconnect application.